Basement membrane collagen IV: Isolation of functional domains - Boudko, Sergei P. (Methods Cell Biol, 2017)
Collagen IV is a major constituent of basement membranes, specialized form of extracellular matrix that provides a mechanical support for tissues, serves as a polyvalent ligand for cell adhesion receptors and as a scaffold for other proteins, and plays a key role in tissue genesis, differentiation, homeostasis, and remodeling. Collagen IV underlies the pathogenesis of several human disorders including Goodpasture’s disease, Alport’s syndrome, diabetic nephropathy, angiopathy, and porencephaly. While the isolation of the collagen IV molecules from tissues is an ultimate prerequisite for structural and functional studies, it has been always hampered by the protein insolubility due to extensive intermolecular crosslinking and noncovalent associations with other components of basement membranes. In this chapter, we present methods for the isolation of collagen IV fragments from basement membranes or from extracellular matrix deposited by cultured cells, and the recombinant expression alternative. These methods are useful to address the fundamental questions on the role of collagen IV in tissue genesis under the normal and pathological conditions.